Rujukan Dan Aplikasi Sistem Hukum Indonesia Berdasarkan Pasal 1 Ayat (3) UUD 1945 Pasca Amandemen Ke Tiga - Hidayat, Nur (UIR Press, 2017)
Law institutions (such as Judges, Lawyer, Police, legislator) as part of important elements in national law system, should know and understand the changes of national law system after the third amandement of UUD 1945, because Indonsia’s law system, that is called Pancasila law system, is integrative law system that takes the best parts of rechtstaat (Europe continental) and the rule of law (Anglo Saxon) that name linking prismatic. Feedback scheme staats with input (interest - social demand - legal act) will be eas to be used by law institution to make output (decision, provision) well. Legal behavior can be a direct response to a legal act. Keywords: Indonesia ‘s law system, reference system, aplication system